On the coordination role of Pyridyl-Nitrogen in the structural chemistry of Pyridyl-Substituted Dithiocarbamate Ligands - Tiekink, Edward R. T. * (MDPI, 2021)
A search of the Cambridge Structural Database was conducted for pyridyl-substituted dithiocarbamate ligands. This entailed molecules containing both an NCS2− residue and pyridyl group(s), in order to study their complexation behavior in their transition metal and main group element crystals, i.e., d- and p-block elements. In all, 73 different structures were identified with 30 distinct dithiocarbamate ligands. As a general observation, the structures of the transition metal dithiocarbamates resembled those of their non-pyridyl derivatives, there being no role for the pyridyl-nitrogen atom in coordination. While the same is true for many main group element dithiocarbamates, a far greater role for coordination of the pyridyl-nitrogen atoms was evident, in particular, for the heavier elements. The participation of pyridyl-nitrogen in coordination often leads to the formation of dimeric aggregates but also one-dimensional chains and two-dimensional arrays. Capricious behaviour in closely related species that adopted very different architectures is noted. Sometimes different molecules comprising the asymmetric-unit of a crystal behave differently. The foregoing suggests this to be an area in early development and is a fertile avenue for systematic research for probing further crystallization outcomes and for the rational generation of supramolecular architectures.